Knowledge creation in networked learning: Combined tools and affordances - Zenios, Maria; Holmes, Brian (Proceedings of the International Conference on Networked Learning, 2010)
Although the pedagogic potential of structured online discussions in higher education has been realised, the promise of rapidly developing wiki technology and synchronous audio and video technology in teaching and learning needs to be examined. A better understanding of the affordances of these tools and a clearer articulation of the kinds of interactions needed for knowledge creation in networked learning is required. This study explores the ways in which knowledge can be jointly created among geographically dispersed communities of developing researchers through combined web-based tools both synchronous and asynchronous enabled though networked technology. We focus on the role online discussion spaces, wikis and synchronous discussions play in collaborative creation of knowledge by looking at participation processes as they occur online and collaboratively. The study is conceived in the broader context of socio-constructivist approach using concepts around the notion of epistemic fluency. The concept of affordance is employed to illuminate the properties inherent in the tools under study and pin point the ways in which they act as facilitators for learning. Qualitative data are generated through a focus group and semi-structured interviews which are triangulated with naturally occurring data from online discussion forums as part of an exploratory case study approach. Analytic techniques using pattern-matching and grounded theory approaches are used in the analysis of the data. Findings suggest that different kinds of networked technologies can support users in multiple and complementary ways when it comes to sharing experiences, exploring concepts and developing new forms of knowledge around key questions and problems. As such, qualitative differences seem to exist in the perceived affordances of online discussion forums and wikis as tools to promote collaborative advancement of knowledge. We suggest that online structured discussion forums provide affordances for probing, interrogating and posing arguments among groups of learners working collaboratively in knowledge creation. Implications suggest switching attention away from wikis as a standalone collaboration tools suitable for educational purposes and turning it on to their functionality as repository spaces for storing and sustaining shared information and collaboratively created knowledge. Evidence pointing to the conditions for successful use of educational wikis identifies affordances of parallel use of synchronous audio and video technology as mediating tools in supporting collaborative wiki-based activity. The combination of wiki with synchronous audio technology seems to offer the necessary affordances for the development of shared meaning and externalisation of individual representations within the group. On this basis, we argue for the necessity for social dialogue in knowledge creation enabled through the implementation of combined tools to offer complementary affordances in the process. Implications of the study place dialogic processes at the centre of educational activities as part of the design of technology-enhanced postgraduate programmes of study across university departments.